Building souls and CVs with a student-run podcasting course - Pohl, Ethan; Liatsis, Emily; Riddell, Jessica (International Journal for Students as Partners, 2018)
This case study discusses an experiential learning course comprising a 12-episode podcast series dedicated to transformative learning in higher education. The three-credit course, which was designed by two student leaders (station managers at the university radio station) in collaboration with a faculty collaborator, was informed by the 10 design principles of authentic learning. The central premise of the podcast series hinged on two key questions: What are the ideal conditions where students build their souls as they build their CVs?; What are the conditions for transformative learning whereby students reflect on their learning experience as collaborators with their professors and with one another? The case study offers recommendations to students, faculty, and educational developers who might integrate this model into their own practices.